Binary Effect of Fly Ash and Waste Glass on Compressive Strength and Heat of Hydration for Concrete - Yet Hui, Lee; Jamellodin, Zalipah; Md Noh, Mohammad Soffi; Adnan, Suraya Hani; Thamrin, Rendy (International Journal of Sustainable Construction Engineering and Technology, 2022)
The most crucial building material in the modern construction industry is concrete. Concrete made of components like cement and aggregates. Cement was a significant contributor to the carbon dioxide emissions that altered the world's climate and had other detrimental effects on the environment. Concrete is used so frequently in the construction industry that it is crucial to conduct research on this topic since it will affect how long a structure lasts. In an effort to decrease the detrimental effects on the environment and enhance the qualities of concrete, alternative materials, such as fly ash (FA) and waste glass (WG), have been utilised to replace some of the fine aggregate and ordinary Portland cement (OPC), respectively. Compressive strength testing and hydration heat assessment were used in this study. Fly ash and waste glass were substituted for normal concrete in amounts ranging from 5 to 25% by weight of the cement and fine aggregate, respectively. For the compressive strength test, 36 concrete cubes with dimensions of 100 mm x 100 mm x 100 mm were created. They were evaluated after 7 and 28 days. Six (6) new concrete samples of 150 mm in diameter and 300 mm in height were prepared in order to access the heat of hydration of concrete. According to the study, the concrete with 5% replacement of FA and WG had the highest compressive strength at both 7 and 28 days, according to the results, out of all the tested mixes. In addition, 13 hours after casting, the control concrete mix design recorded the 37°C peak temperature, which was the highest of all the concrete mixes.